Dual characteristics of molybdenum disulfide based PN heterojunction photodetector prepared via drop-cast technique - Ahmad, Harith; Thandavan, Tamil Many K.; Thambiratnam, Kavintheran (Elsevier, 2019)
A p-silicon/molybdenum disulfide (p-Si/MoS2) p-n heterojunction photodetector (PD) is proposed and fabricated using the drop-casting technique. The composition of elements in the localized surface morphology enables for excellent photoconduction under 380 nm illumination at various ultraviolet (UV) powers. The uneven and even distribution of the current-voltage I-V curve in the negative and positive bias regions indicate substantial dual characteristics in the fabricated device. A high responsivity of about 9.6 and 0.388 AW−1 is measured at the negative and positive bias regions respectively, allowing the p-Si/MoS2 p-n heterojunction PD to operate at UV powers lower than 830 μW. © 2019 Elsevier GmbH